Prospects and Challenges in Developing mRNA Vaccines for Infectious Diseases and Oncogenic Viruses - Lakshmi Venkata Simhachalam Kutikuppala; Islam Kourampi; Ramya S. D. Kanagala; Priyadarshini Bhattacharjee; Sri Harsha Boppana (Medical Sciences, 2024)
mRNA vaccines have emerged as an optimistic technological platform for vaccine innovation in this new scientific era. mRNA vaccines have dramatically altered the domain of vaccinology by offering a versatile and rapid approach to combating infectious diseases and virus-induced cancers. Clinical trials have demonstrated efficacy rates of 94–95% in preventing COVID-19, and mRNA vaccines have been increasingly recognized as a powerful vaccine platform. Although mRNA vaccines have played an essential role in the COVID-19 pandemic, they still have several limitations; their instability and degradation affect their storage, delivery, and over-all efficiency. mRNA is typically enclosed in a transport mechanism to facilitate its entry into the target cell because it is an unstable and negatively charged molecule. For instance, mRNA that is given using lipid-nanoparticle-based vaccine delivery systems (LNPs) solely enters cells through endocytosis, establishing an endosome without damaging the cell membrane. The COVID-19 pandemic has accelerated the development of mRNA vaccine platforms used to treat and prevent several infectious diseases. This technology has the potential to change the future course of the disease by providing a safe and effective way to combat infectious diseases and cancer. A single-stranded genetic sequence found in mRNA vaccines instructs host cells to produce proteins inside ribosomes to elicit immunological responses and prepare the immune system to fight infections or cancer cells. The potential applications of mRNA vaccine technology are vast and can lead to the development of a preferred vaccine pattern. As a result, a new generation of vaccinations has gradually gained popularity and access to the general population. To adapt the design of an antigen, and even combine sequences from different variations in response to new changes in the viral genome, mRNA vaccines may be used. Current mRNA vaccines provide adequate safety and protection, but the duration of that protection can only be determined if further clinical research is conducted.